[Davao weaver] - Philippines. National Commission for Culture and the Arts. (Manila NCCA)
A documentation of the traditional art of Mandaya weaving. It features the demonstration and interview with a Gamaba candidate.
VHS.
Keywords: Weaving -- Philippines -- Davao; Mandayas